Virtual Game Jam: Collaborative Pathway to Serious Games for Health - Sarah Matthews; Rick Thomas (Serious Games Society, 2022)
Game jams are collaborative competitions where participants make games from scratch within a short period of time. Occasionally, these games aim to promote meaningful learning outcomes by embedding functional knowledge into entertaining and engaging gameplay.  We wanted to understand if a game jam during a global pandemic could be used as an effective method to facilitate a collaborative, multidisciplinary team's ability to design, develop, and implement a serious game on a health-related topic (i.e., COVID-19).  We examined the 2020 game jam hosted by the National Academy of Sciences to evaluate one method to organize a serious virtual game jam and provide a roadmap for implementation using qualitative and quantitative data collection methods to evaluate its efficacy. In addition to identifying best practices and lessons learned from our tools and processes, our results demonstrate that a virtual game jam can in fact be a powerful tool for creating a scientifically sound, population-level, big picture-thinking serious game used for health education, facilitate collaborative multidisciplinary teams and be a practical learning experience for game jammers.